Effect of growth hormone treatment on children with idiopathic short stature (ISS), idiopathic growth hormone deficiency (IGHD), small for gestational age (SGA) and Turner syndrome (TS) in a tertiary care center - Al Shaikh, Adnan; Daftardar, Hadeer; Alghamdi, Abdul Aziz; Jamjoom, Majd; Awidah, Saniah; Ahmed, Mohamed E; Soliman, Ashraf T (Acta Biomedica Atenei Parmensis, 2020)
Objectives: To assess the long-term effect of growth hormone (GH) therapy in a large cohort of short children with different etiologies. Patients and Methods: We evaluated retrospectively the anthropometric data of 252 short children [height SDS